The Emergence of Verification (taḥqīq) in Islamic Medicine: The Exegetical Legacy of Faḫr al-Dīn al-Rāzī’s (d. 1210) Commentary on Avicenna’s (d. 1037) Canon of Medicine - Karimullah, Kamran I. (Oriens, 2019)
Abstract In this article, I discuss the legacy of Faḫr al-Dīn al-Rāzī’s commentary on Avicenna’s Canon of Medicine in Islamic medical commentary after 1100. I argue that Faḫr al-Dīn’s legacy lies in the exegetical practices, the method of verification (taḥqīq) he introduced into Islamic medical scholarship through his commentary on the Canon. I first argue that the features that characterise the method of verification in works such as Faḫr al-Dīn’s commentary on Avicenna’s Pointers and Reminders are present in the commentary on the Canon, even if Faḫr al-Dīn’s introduction to the latter work does not allude to these practices in the way that the introductions to his later works do. Based on an analysis of Galen’s prescription about exegetical best-practice in his Hippocratic commentaries and Muḥammad ibn Zakarīyā al-Rāzī’s (d. ca. 925) introduction to Doubts on Galen, I argue next that Faḫr al-Dīn’s introduction of the verification method into the Islamic medical discourse was a watershed moment in the tradition. I use Ibn al-Quff’s (d. 1286) commentary on the Hippocratic Aphorisms to show how these methods were imitated by later medical commentators. This final section illustrates the enormous exegetical interest that the Canon of Medicine attracted, suggesting other promising trajectories for research into Faḫr al-Dīn’s medical legacy.